Modifiable Factors Associated with Quality of Bowel Preparation Among Hospitalized Patients Undergoing Colonoscopy. Issue 5 (8th April 2019) - Garber, Ari; Sarvepalli, Shashank; Burke, Carol A; Bhatt, Amit; Ibrahim, Mounir; McMichael, John; Morris‐Stiff, Gareth; Rizk, Maged K; Vargo, John J; Rothberg, Michael B
Abstract : INTRODUCTION: Inadequate bowel preparation (IBP) is a common problem in hospitalized patients; however, little is known about how to prevent IBP. In a large, multihospital system, we evaluated the association between modifiable factors and IBP rate. METHODS: We reviewed data from adult (≥18 years) inpatients undergoing colonoscopy between January 2011 and June 2017. Colonoscopies performed in the intensive care unit or lacking descriptions of bowel preparation quality were excluded. Multivariate logistic regression analysis was performed to identify factors associated with IBP. A counterfactual analysis was performed to assess the potential contribution of modifiable factors to IBP. RESULTS: Of 8, 819 patients that were included (median age of 64 years; 50.5% female), 51% had IBP. Patients with IBP stayed in the hospital one day longer than those with adequate bowel preparation ( P < .001). Modifiable factors associated with IBP include opiate use within three days of colonoscopy (OR, 1.31; 95% CI, 1.18, 1.45), colonoscopy performed after 12:00 pm (OR, 1.25; 95% CI, 1.1, 1.41), and solid diet the day before colonoscopy (OR, 1.37; 95% CI, 1.18, 1.59). In the counterfactual analysis, if all patients avoided these three conditions, adjusted IBP rates were reduced by 5.6%. CONCLUSIONS: Among hospitalized patients undergoing colonoscopy, IBP rates are high and associated with an increased length of stay. Avoiding opiates before colonoscopy, performing colonoscopy before noon, and maintaining patients on a liquid diet or nil per os might significantly reduce IBP rates.